The effect of candida albicans on some blood and biochemical parameters in laboratory mice .: Hanan Abdel Reda Mohammed , Iqbal Abdel Aziz H A Zam , Mohammed Hassan Khadr - Mohammed, Hanan Abdel Reda (The Iraqi Journal of Veterinary Medicine, 2005)
In the present study , 32 white mice Balb /C (two months age ) were used ,therewere divided into four equal groups . Three groups were injected with fungalsuspention of candida albicans in doses of 1x106 ,1x108 and 3x108 cell/ml,whereas the fourth group was regarded as control and injected with 0.5 mlnormal saline solution . All were dissected after 6 days of injection to study thephysiological effect of the yeast on blood , which include RBCand WBC count ,Hb concentration and PCV ratio . And on biochemical content whichinclude the determination of protein , glycogen and cholestrol in liver ,kidneyand muscles .The results showed that the number of RBC were decreased ,while WBCwere increased in the injected mice ,but there were no signifficant effect onPCV and Hb . On the other hand ,cholestrol values were decreased significantlyin the injected mice in comparison with control,but this decrease was varied indifferent tissues (P>0.01).The value was lower in liver ,whereas no signifficantdifference was found between Kidney and muscles . Protein values were notsignifficantly different in comparison with control , but it was different amongtissue studied .muscles was the highest value and the liver was lowest .Glycogen decreased signifficantly in comparison with control ,but not amongtissues.